2021
DOI: 10.3390/ijms22041535
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Non-Ionic Surfactant Carrier-Based Gel for Topical Delivery of Desoximetasone

Abstract: Psoriasis is a chronic autoimmune skin disease impacting the population globally. Pharmaceutical products developed to combat this condition commonly used in clinical settings are IV bolus or oral drug delivery routes. There are some major challenges for effectively developing new dosage forms for topical use: API physicochemical nature, the severity of the disease state, and low bioavailability present challenges for pharmaceutical product developers. For non-severe cases of psoriasis, topical drug delivery s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…The HPLC analysis of the loaded formulations showed a loading capacity of RK in β-CD PYRO of 8.02 ± 0.51% and 8.50 ± 0.45% for LC PYRO NSs while the encapsulation efficiency calculated was 88.62 ± 1.05% and 89.71 ± 0.86% for β-CD PYRO and LC PYRO NSs, respectively. These values are in accordance with previous drugs complexes such as stilbenes or kynurenic acid for other types of NSs [ 29 , 30 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The HPLC analysis of the loaded formulations showed a loading capacity of RK in β-CD PYRO of 8.02 ± 0.51% and 8.50 ± 0.45% for LC PYRO NSs while the encapsulation efficiency calculated was 88.62 ± 1.05% and 89.71 ± 0.86% for β-CD PYRO and LC PYRO NSs, respectively. These values are in accordance with previous drugs complexes such as stilbenes or kynurenic acid for other types of NSs [ 29 , 30 ].…”
Section: Resultssupporting
confidence: 91%
“…The presence of cyclodextrin units within the nanogel structure can promote the hydrophobic drug incorporation [ 24 , 29 , 30 , 31 , 32 ]. β-CD nanosponges (NSs) are chemically crosslinked polymers that have many attractive features for use as hydrogels.…”
Section: Resultsmentioning
confidence: 99%
“…The cumulative release of TBH from the control and nano-gel formulations is plotted against time in Figure 10 a; it can be noted that the cumulative amount of drug released from the two types of gels was similar at the end of the 24-h IVRT study. However, the drug release profiles show that the control gel showed a higher release early on in the study, and started to plateau towards the end; whereas the TBH nano-gel showed a controlled release over time and appeared to gradually build up the drug load in the receptor media, and did not appear to have plateaued at 24 h. The drug release profile from TBH nano-gel was found to obey Higuchi’s square root diffusion model, as shown in Figure 10 b, with a correlation coefficient (r 2 ) of 0.99 [ 80 , 81 ]. The data fitting was based on Equation (6) as described by the Higuchi model: where Q is the amount of drug released in time t , and K H is the Higuchi constant.…”
Section: Resultsmentioning
confidence: 96%
“…In general, the solubility of non-ionic surfactants in water is not good compared with the solubility of ionic surfactants; however, they do not change the pH of the solution. Usually, these surfactants show a better biocompatibility than ionic ones, making them suitable for biomedical applications [17][18][19][20]. The non-ionic surfactants are also the most used in the food industry [21][22][23].…”
Section: Non-ionic Surfactantsmentioning
confidence: 99%